2010
DOI: 10.1152/jn.00194.2010
|View full text |Cite
|
Sign up to set email alerts
|

Changes in S1 Neural Responses During Tactile Discrimination Learning

Abstract: In freely moving rats that are actively performing a discrimination task, single-unit responses in primary somatosensory cortex (S1) are strikingly different from responses to comparable tactile stimuli in immobile rats. For example, in the active discrimination context prestimulus response modulations are common, responses are longer in duration and more likely to be inhibited. To determine whether these differences emerge as rats learned a whisker-dependent discrimination task, we recorded single-unit S1 act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
75
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(87 citation statements)
references
References 49 publications
11
75
1
Order By: Relevance
“…Interhemispheric connections between the barrel fields were described by Olavarria et al (1984) and Koralek et al (1990) in the rat, who found that they are confined to the septal regions. The work on unanesthetized rats by Shuler et al (2001) and Wiest et al (2010) found a proportion of units that responded to stimulation of vibrissae from either side of the muzzle in layer V of the barrel cortex. Bilateral subthreshold receptive fields were also described in that layer by Manns et al (2004).…”
Section: Discussionmentioning
confidence: 99%
“…Interhemispheric connections between the barrel fields were described by Olavarria et al (1984) and Koralek et al (1990) in the rat, who found that they are confined to the septal regions. The work on unanesthetized rats by Shuler et al (2001) and Wiest et al (2010) found a proportion of units that responded to stimulation of vibrissae from either side of the muzzle in layer V of the barrel cortex. Bilateral subthreshold receptive fields were also described in that layer by Manns et al (2004).…”
Section: Discussionmentioning
confidence: 99%
“…By lowering the minimal synaptic input required to generate cell firing, LLPIE could contribute to the strengthening of cortical responsiveness observed following repeated coactivation of specific whiskers or behavioral training (Diamond et al, 1994;Wiest et al, 2010). In addition, as shown in hippocampus (Cudmore et al, 2010), the enhanced spike-time precision after LLPIE induction could increase the propensity for synchronization in the cortical network.…”
Section: Functional Implications Of Bidirectional Intrinsic Plasticitymentioning
confidence: 99%
“…In the adult somatosensory cortex, the preferential use of a subset of whiskers (Diamond et al, 1993;1994), or the pairing of whisker stimuli with positive or negative reinforcement (Siucinska and Kossut, 1996;, alter the neuronal responses to the trained whiskers. Changes in responsive properties of layer 5 cortical neurons also occur during learning of a whisker-dependent discrimination task and contribute to improvement in the discrimination performance (Wiest et al, 2010). This adaptation of cortical responsiveness likely involves plasticity of synaptic connections within the different layers of barrel cortex (Fox, 2002;Jacob et al, 2007, Skibinska-Kijek et al, 2008Feldman, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although the behaviour strategy used by the animal ('active sensing' versus 'detection amid distractors') 22,24 cannot be distinguished, our activation patterns are in line with previous reports indicating that S1-M1 integration may inform the decision of the mouse under this task condition [18][19][20] . As sensory stimulus features alone are not sufficient to produce these differential activation patterns among S2P and M1P neurons, we speculate that other mechanisms could be involved, including plasticity of local and long-range circuits during task learning 27,28 or topdown influences exerted by feedback circuits or attention-related brain areas during task engagement 29,30 . Understanding the circuits and mechanisms underlying this selective routing of sensory information will warrant further investigation.…”
mentioning
confidence: 99%